2020
DOI: 10.1016/j.apergo.2019.103012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of breast size and bra type on comfort for UK female police officers wearing body armour

Abstract: Within the Police service of England and Wales the wearing of ballistic and stab resistant body armour is common, with most police forces mandating its usage when away from the police station. Of all the serving police officers in England and Wales 29.1% are female (Hargreaves et al., 2017). A survey was developed and then distributed by the Police Federation of England and Wales to all servicing police officers up to the rank of Inspector. The survey returned 2633 responses after cleaning of the data. From th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
1
12
0
2
Order By: Relevance
“…The resultant compression and deformation of the breast when wearing body armour, which is exaggerated in women with large breasts (McGhee and Steele, 2020 ), is likely to have negative functional and protection impacts (e.g., difficulty breathing, limited ROM, exposed lateral breast tissue, and compromised positioning of vital torso protection). Consequently, our findings corroborate previous reports that occupational body armour does not adequately accommodate the full range of female breast characteristics (Coltman et al, 2020 , 2021a ; Malbon et al, 2020 ; Niemczyk et al, 2020 ). It was therefore unsurprising that Breast Volume, Breast Surface Area and Anterior Breast Projection were each associated with the perception of poor body armour fit ( Table 6 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The resultant compression and deformation of the breast when wearing body armour, which is exaggerated in women with large breasts (McGhee and Steele, 2020 ), is likely to have negative functional and protection impacts (e.g., difficulty breathing, limited ROM, exposed lateral breast tissue, and compromised positioning of vital torso protection). Consequently, our findings corroborate previous reports that occupational body armour does not adequately accommodate the full range of female breast characteristics (Coltman et al, 2020 , 2021a ; Malbon et al, 2020 ; Niemczyk et al, 2020 ). It was therefore unsurprising that Breast Volume, Breast Surface Area and Anterior Breast Projection were each associated with the perception of poor body armour fit ( Table 6 ).…”
Section: Discussionsupporting
confidence: 91%
“…In the same study 29–59% of participants experienced task interference during a range of basic job roles (Davis et al, 2020 ). Another group found that integration between a soldier's bra and body armour was a source of substantial discomfort (Malbon et al, 2020 ). The notion of sex-specific discomfort with body armour was supported by findings from an Australian study, which revealed that limited adjustability of the system, insufficient space for breasts and oversized length and width were all common problems reported by female soldiers (Coltman et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has demonstrated that female police officers found body armour uncomfortable to wear, particularly around the breast area, and some actions such as self-defence techniques and driving a car were difficult to perform (Malbon et al, 2020). An investigation into female British soldiers wearing the OSPREY armour system, reported similar findings (Davis et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A previous study identified the most common styles of bras worn by police officers under body armour were underwired (71%) and sports (17%) bras (Malbon et al, 2020). For this study, each participant attended a professional bra fitting session and was fitted for a new underwired and sports bra.…”
Section: Bra Fittingmentioning
confidence: 99%